Wind age, wolf age - Crago, Hugh, 1946- (Port Adelaide, [South Australia] : Ginninderra Press, 2017)
"The earliest poems I produced were fierce jabs at the many things that irritated me about the world in which I now lived. Some of them have survived in the section of this volume that I've called Aspirational Lifestyles. Others (Nacht und Nebel) were responses to the harsh beauty of the upper Blue Mountains, where my wife and I have lived for the past seventeen years. An increasing number (Dream Country) took their inspiration from the cinema of the unconscious (I sometimes wake from dreams with intriguing images, and a line or two that later turns into a poem). But most of all, I found myself writing about old age (Towards Winter). It's not a popular subject for writers generally, nor is it likely to find a wide audience among younger readers, who are understandably reluctant to look too closely at what is to come." -- Back cover.
Keywords: Australian poetry -- 21st century; Australian